2023
DOI: 10.3389/frma.2023.943228
|View full text |Cite
|
Sign up to set email alerts
|

A study on the content of integrity policies and research integrity management in Chinese universities

Abstract: BackgroundThis study outlines a comprehensive analysis of the primary characteristics of managing research integrity (RI) in domestic colleges and universities in China. RI education in China consists primarily of soft advocacy, with no hard requirements or continuous and systematic support. Together with other stakeholders, such as funders and publishers, higher education institutions (e.g., colleges and universities) are one of the vital actors that have a lot of influence on RI promotion and implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The referred results are supported by the study that identified similar environments (Roje et al, 2022) The category (IR policy) refers to a set of guidelines and standards developed by institutions to promote responsible research and prevent FFP and QRP. The study found that there were studies that proposed various ideas for institutions to promote and implement their research, training and education policies to conduct responsible research, and identified various actors to ensure the quality of research and the integrity culture, explaining that research is not only the responsibility of individual researchers or groups, but also that of other actors (such sponsors, mentors, supervisors, institutions and research-related systems) provide the conditions for ensuring the quality of scientific production (Cao et al, 2023;Helgesson & Bülow, 2021;Meriste et al, 2016;Roje et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The referred results are supported by the study that identified similar environments (Roje et al, 2022) The category (IR policy) refers to a set of guidelines and standards developed by institutions to promote responsible research and prevent FFP and QRP. The study found that there were studies that proposed various ideas for institutions to promote and implement their research, training and education policies to conduct responsible research, and identified various actors to ensure the quality of research and the integrity culture, explaining that research is not only the responsibility of individual researchers or groups, but also that of other actors (such sponsors, mentors, supervisors, institutions and research-related systems) provide the conditions for ensuring the quality of scientific production (Cao et al, 2023;Helgesson & Bülow, 2021;Meriste et al, 2016;Roje et al, 2022).…”
Section: Discussionmentioning
confidence: 99%